Prevalence and etiology for mandibular and mid-face bone fractures in a tertiary care hospital - Arakkal Nellissery Chakkappan John; Thekkuttuparambil Ananthanarayanan Ajith (Archives of Clinical and Experimental Surgery, 2017)
Background: The rate of mandibular and mid-face bone fracture was found to vary among the population. This study sought to find out the prevalence of mandibular and mid-face bone fractures in a tertiary care hospital. Methods: A retrospective study was conducted over the period of three years. Subjects aged 5-80 years with mandibular and mid-face bone fractures admitted for surgical intervention were included. Type, pattern and major etiological factors for bone fracture were accounted for and subjected to statistical analysis. Results: Among the 103 cases, mandibular fracture was observed in 72 cases (45 single and 27 combined bones) with male dominance (69 males and 3 females; 23:1 ratio). The mid-face bone fractures were found in 41 cases within the male group (32 single and 9 combined bones). For the mandibular and mid-face bone fractures, the most prevalent age groups were the 19-29 and 30-49 years, respectively (p = 0.80). The parasymphysis/body (33%) and condyle/ramus (20%) were the bone fracture among the mandible observed with the highest frequency, while that of the mid-face bone was for the maxilla (43.7%) and zygoma (31.2%). Road traffic accidents (RTAs) were the major cause of these sorts of fractures in the 19-29 age group (62%; p = 0.001). Conclusion: The mandible was the single most common site of bone fracture because of RTAs in males 19-29 years of age. This emphasizes the need for public health awareness so that people follow general traffic rules and road safety measures. Prevalence was found to vary based on socioeconomic, cultural, and behavioral variations among the populations. [Arch Clin Exp Surg 2017; 6(4.000): 183-188]